Erectile dysfunction in patients of diabetes mellitus: a cross sectional study - Bellad, Anilkumar; Sahu, Kartik (International Surgery Journal, 2019)
Background: One of the independent risk factor for erectile dysfunction is diabetes mellitus. The present study planned to determine the prevalence and factors associated with ED in DM. Methods: A one year cross-sectional study on a total of 208 patients with type 1 or 2 diabetes. National Institutes of Health (NIH) approved questionnaire for International Index of Erectile Function (IIEF) was used to interview each patient to assess for ED. Results: In this study 12.98% of patients had ED score between 13 to 18 suggestive of mild to moderate ED and 9.62% with 19 to 24 scores suggestive of mild degree. The prevalence of erectile dysfunction was 32.21%. The mean age in patients with erectile dysfunction was significantly high (58.40±10.96 years) compared to those without erectile dysfunction (51.00±11.16 years) (p<0.001) Of the 119 patients with duration of diabetes between one to five years 42.02% had ED and of the 3 patients with duration of more than five years 66.67% had ED (p<0.001). Prevalence of ED was higher in patients with HbA1c levels between 7.0 to 8.5 (32.76%) and >8.5 (37.07%). Prevalence of erectile dysfunction was higher in patients with history of smoking (63.64%) (p<0.001) and alcohol intake (51.85%) (p<0.001). The prevalence of erectile dysfunction was also significantly high in patients with history of hypertension (59.7%) (p<0.001). Conclusions: The ED in patients with diabetes mellitus was significantly prevalent with age, duration of diabetes, history of hypertension, cardiovascular disease, glycemic control and hypertriglyceridemia.